Morphometric Studies on Subadult Liza subviridis and Sillago sihama from Sonmiani Bay (Miani Hor), Balochistan, Pakistan - Muhammad A. Gondal; Naureen A. Qureshi; Noor U. Saher (Journal of Bioresource Management, 2014)
Length-weight relationship of Liza subviridis and Sillago sihama (Family: Mugilidae; Class: Pisces and Family: Sillaginidae; Class: Pisces) in subadults sampled from Somiani Bay Balochistan, Pakistan during 2002, 2003􀀃and 2006 was analyzed. Liza subviridis showed positive allometry (3.23) in 2002, and n􀁈gative allometry during 2003 (2.95) and 􀀕􀀓􀀓􀀙􀀃 (1.95). Sub adults of Sillago sihama showed positive allometry during 2002 (3.10) and 2003 (3.13). An isometric condition (3.02) was observed in the samples of Sillago sihama collected from Bhaira in 2006.